PERKEMBANGAN PSIKOSOSIAL ANAK USIA DINI YANG MENGALAMI KETERLAMBATAN DALAM BERBICARA - Oktaviani Puspita, - (2022)
Early childhood is the most important period for all of his life, because early childhood is a period of formation and the basis of personality that will determine subsequent experiences. This is so important that the needs of early childhood must be met. Experts from various fields, including education, child psychologists and nutritionists, see that it is very important to give gifts and fulfill the needs of early childhood. Psychosocial development is a development that will not be separated until the end of life or can be said to be a lifelong process because in psychosocial development, everything we learn at the beginning of the first year of life will determine and shape the pattern of further development. speech delay, where the mother realized early on when the child didn't chatter much and said a lot of words at the age of 2 years. This research uses a case study approach method and only involves one child to observe and find information about the psychosocial development of early childhood who have speech delays. The results of the study indicate that the psychosocial development of early childhood begins with the child's early development process, then the environment around the child as well as perceptions about the child's own psychosocial development and the obstacles that have an impact on his psychosocial development.